A Surgical Procedure for the Administration of Drugs to the Inner Ear in a Non-Human Primate Common Marmoset (Callithrix jacchus) - Kurihara, Sho (J Vis Exp, 2018)
Hearing research has long been facilitated by rodent models, although in some diseases, human symptoms cannot be recapitulated. The common marmoset (Callithrix jacchus) is a small, easy-to-handle New World monkey which has a similar anatomy of the temporal bone, including the middle ear ossicular chains and inner ear to humans, than in comparison with that of rodents. Here, we report a reproducible, safe, and rational surgical approach to the cochlear round window niche for the drug delivery to the inner ear of the common marmoset. We adopted posterior tympanotomy, a procedure used clinically in human surgery, to avoid manipulation of the tympanic membrane that may cause conductive hearing loss. This surgical procedure did not lead to any significant hearing loss. This approach was possible due to the large bulla structure of the common marmoset, although the lateral semicircular canal and vertical portion of the facial nerve should be carefully considered. This surgical method allows us to perform the safe and accurate administration of drugs without hearing loss, which is of great importance in obtaining pre-clinical proof of concept for translational research.